Bioavaibility Evaluation and Molecular Docking of Cananga odorata Plant as Anti-Inflammatory Potential Against Crohn’s Disease - Annisadila, Shindy; Jamil, Ahmad Shobrun; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2478, 2023)
Crohn's disease is a chronic inflammatory bowel disease (IBD) that affects the digestive tract. One of the potential targets for this disease is LRRK2. Kenanga ( Cananga odorata ) is known to have anti-inflammatory effects. The study aims to identify the potential of the secondary metabolite compounds found in C. odorata against LRRK2 in silico. The KnapSack database was used to identify the secondary metabolite compounds of C. odorata , SwissADME was used to find the compound with high bioavailability with the Boiled-EGG method, and PyRx with the AutoDock was used for molecular docking. According to the docking results, three compounds are potentially inhibiting LRRK2, namely (+)-Reticuline with a binding energy of -9.04 kcal/mol and a prediction of inhibition constant (pKi) of 237.71 nM, benzyl benzoate with a binding energy of -8.19 kcal/mol and a prediction of inhibition constant (pKi) of 994.29 nM and benzyl salicylate with a bonding energy of -8.22 kcal/mol and a prediction of inhibition constant (pKi) of 942.48 nM.